2019
DOI: 10.1007/s11356-019-04625-0
|View full text |Cite
|
Sign up to set email alerts
|

Controllable synthesis of Fe3O4-wollastonite adsorbents for efficient heavy metal ions/oxyanions removal

Abstract: Iron oxide, in the form of magnetite (MG)-functionalized porous wollastonite (WL), was used as an adsorbent for heavy metal ions (cadmium and nickel) and oxyanions (chromate and phosphate) removal from water. The porous WL was synthesized from calcium carbonate and siloxane by controlled sintering process using low molecular weight submicrosized poly(methyl methacrylate) as a pore-forming agent. The precipitation of MG nanoparticles was carried out directly by a polyol-medium solvothermal method or via branche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 83 publications
0
30
0
Order By: Relevance
“…The results presented in Table 2 show an increase of adsorption capacity as the temperature increases, while Langmuir constant remains constant and very slightly increases at the highest temperature. According to the Langmuir isotherm, assumed mechanism of chromate anions adsorption is attributed to the monolayer adsorption with equal enthalpy and energy for all reactive sites [6]. Obtained negative ΔG° values from -35.06 to -37.80 kJ mol -1 indicate that adsorption occurs via spontaneous reactions followed by both physisorption and chemisorption mechanisms [6].…”
Section: Adsorption Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results presented in Table 2 show an increase of adsorption capacity as the temperature increases, while Langmuir constant remains constant and very slightly increases at the highest temperature. According to the Langmuir isotherm, assumed mechanism of chromate anions adsorption is attributed to the monolayer adsorption with equal enthalpy and energy for all reactive sites [6]. Obtained negative ΔG° values from -35.06 to -37.80 kJ mol -1 indicate that adsorption occurs via spontaneous reactions followed by both physisorption and chemisorption mechanisms [6].…”
Section: Adsorption Resultsmentioning
confidence: 99%
“…The point of zero charge of the synthesized LMS-NM adsorbent was determined by the pH drift method. This analysis is undertaken to explore the influence of pH on the state of equilibrium of ionic/anionic species and protonation/deprotonation of LMS-NM functional groups [6].…”
Section: Point Of Zero Chargementioning
confidence: 99%
See 1 more Smart Citation
“…For a favorable isotherm, R L is between 0 and 1, for an irreversible isotherm R L is zero, for linear isotherms R L =1 and unfavorable isotherms R L >1 . Table illustrates the parameters of the Langmuir isotherm for CrO 4 2− and NO 3 − at different concentrations of these ions in the range of 15–75 mg L −1 for 10 mL of an aqueous solution using 10 mg of the adsorbent.…”
Section: Langmuir Isothermmentioning
confidence: 99%
“…The correlation coefficients, as opposed to those of the Langmuir model, were indicated that this isotherm model is not suitable for predicting the adsorption equilibria of CrO 4 2− and NO 3 − . Further n values of over 1 show that the adsorption condition is favorable …”
Section: Langmuir Isothermmentioning
confidence: 99%